2018
DOI: 10.1038/s41598-018-22939-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Great Pacific Garbage Patch is rapidly accumulating plastic

Abstract: Ocean plastic can persist in sea surface waters, eventually accumulating in remote areas of the world’s oceans. Here we characterise and quantify a major ocean plastic accumulation zone formed in subtropical waters between California and Hawaii: The Great Pacific Garbage Patch (GPGP). Our model, calibrated with data from multi-vessel and aircraft surveys, predicted at least 79 (45–129) thousand tonnes of ocean plastic are floating inside an area of 1.6 million km2; a figure four to sixteen times higher than pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
807
1
33

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,304 publications
(865 citation statements)
references
References 52 publications
24
807
1
33
Order By: Relevance
“…Several studies have reported a correlation between the size of plastics and their rising velocity (Kooi et al, 2016;Lebreton et al, 2018;Reisser et al, 2015). Chubarenko et al (2016) determined the windage coefficient of plastics based on size and density, and Lebreton et al (2018) derived a windage coefficient for plastics in the North Pacific garbage patch by using it as a calibration parameter for their numerical model. Despite these efforts there is no generally applicable method to relate material properties to relevant transport properties of plastics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported a correlation between the size of plastics and their rising velocity (Kooi et al, 2016;Lebreton et al, 2018;Reisser et al, 2015). Chubarenko et al (2016) determined the windage coefficient of plastics based on size and density, and Lebreton et al (2018) derived a windage coefficient for plastics in the North Pacific garbage patch by using it as a calibration parameter for their numerical model. Despite these efforts there is no generally applicable method to relate material properties to relevant transport properties of plastics.…”
Section: Discussionmentioning
confidence: 99%
“…Moore et al (2001) first observed a garbage patch in the North Pacific Ocean. Since then, several sampling studies have confirmed the existence of garbage patches in both the North Pacific and the North Atlantic oceans (Lebreton et al, 2018;van Sebille et al, 2015). There are fewer sampling studies in the Southern Hemisphere, but a sharp gradient in the measured plastic concentration suggests that there is a garbage patch in the South Pacific Ocean as well (Eriksen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Data from 24 oceanic expeditions suggest that the total amount of ocean plastic pollution was at a minimum of 5.25 trillion pieces weighing over 250,000 tons (Eriksen et al, 2014). However, more recent estimates based on the Great Pacific Garbage Patch suggest that the amount of plastic may be four to 16 times higher than previous estimates (Lebreton et al, 2018). If other areas of the ocean have accumulated plastic at a similar or faster rate, then the global total may be much higher than previously estimated.…”
Section: Marine Plastic Pollution Is a Global Threat To Biodiversitymentioning
confidence: 88%
“…The U.S. plastic waste stream informed by Jambeck et al (), Brooks, Wang, and Jambeck (), EPA (), Lebreton et al (), and Penca (2018). Illustrated by Erin Cinkant…”
Section: Single‐use Plastics Fishing Nets and The United States: Thementioning
confidence: 99%
“…The role of long‐distance dispersal in population expansion is historically difficult to enumerate, but evidence from the Japanese tsunami of 2011 shows that a wide variety of marine organisms are able to survive for years adrift on debris across more than 7,000 km of ocean (Carlton et al, ). As the amount of oceanic debris continues to increase (Eriksen et al, ; Lebreton et al, ), this dispersal mechanism is likely to grow in prevalence and may lead to increased likelihood of species invasions. Dispersal is a critical first step to population establishment, but on arrival, individuals surviving oceanic transport on debris face several barriers to population growth (Blackburn et al, ; Carlquist, ).…”
Section: Discussionmentioning
confidence: 99%